Relevansi Program Revegetasi Hutan Mangrove dengan Nilai Ekoteologi Islam di Desa Baddurih Pademawu Pamekasan - Sholahuddin Qoffal; Siswanto Siswanto; Emna Laisa; Moh Elman; Fajar Habibullah (Attractive : Innovative Education Journal, 2026)
This study aims to analyze the stages of the mangrove forest revegetation program, the contributions of village officials, and its relevance to the values of Islamic ecotheology in Baddurih Village, Pademawu District, Pamekasan Regency. A qualitative descriptive approach was employed. Data were collected through semi-structured interviews, non-participant observation, and documentation. The data were analyzed using the Miles and Huberman model, which consists of data reduction, data display, and conclusion drawing, while the validity of the findings was ensured through source and technique triangulation. The findings reveal that the mangrove revegetation program was implemented through four main stages: site preparation, seedling procurement, planting, and maintenance, all of which were carried out in a participatory manner. Village officials played significant roles as planners, coordinators, facilitators, and financial managers throughout the program. Furthermore, the program demonstrates strong relevance to Islamic ecotheological values, including trustworthiness and responsibility (Amanah), balance (Mizan), restoration and improvement (Ishlah), compassion (Rahmah), and beauty (Jamal). Therefore, the program represents not only an ecological conservation effort but also the practical implementation of religious values in environmental stewardship. This study contributes to a more conceptual understanding of conservation practices among coastal communities as an explicit form of worship. Such an approach is considered effective in enhancing environmental awareness and concern, particularly among Muslim coastal communities, regarding the importance of preserving mangrove ecosystems.